Methods for Developing Smart City Systems in Uzbekistan - Rakhmatullaev Valijon Farkhadovich (Periodica Journal, 2024)
In this article, we analyze the development of smart city systems in Uzbekistan. The trends and perspectives of integrating information and communication technologies (ICT) into urban environments in Uzbekistan are examined. The criteria of trust, transparency, and accountability, specific to corporate governance, are gaining importance in improving the investment environment, ensuring financial stability, and promoting sustainable economic growth
Keywords: smart city; ICT; financial stability